The Relationship Between Head Teachers’ School Rules’ Implementation and Student Academic Performance In Secondary Schools (Journal of Namibian Studies : History Politics Culture, 2023)
This study examined the relationship between head teachers' enforcement of school rules and students' academic achievement in private secondary schools. The school rules and academic performance are interrelated and key to the realization of good performance. The goal of this study was to ascertain how the application of school rules and regulations by head teachers and students’ academic achievement are related to one another in secondary schools in Mogadishu, Benadir region. The theories X and Y put out by Douglas McGregor were the focus of this study. The intended populations consists of 2040 students from eight secondary schools, 68 instructors who serve on disciplinary committees, and 34 head teachers. Thus, there were 2142 target populations in total. 307 respondents made up the sample, and they were distributed as follows: 8 head teachers, 8 teachers who serve on disciplinary committees, and 291 fourth-grade pupils from the 8 chosen schools are included. The validity of the content was assessed using professional judgment. The test-retest approach was used to determine the instrument reliability. By using professional judgment, the validity of the questionnaire was guaranteed. The information was gathered through questionnaires and interview schedules. The descriptive statistics used specifically for quantitative data analysis using SPSS were frequencies, percentages, means, and standard deviation. Frequency tables, bar graphs, and charts were used to display the study's findings. Themes derived from the objectives were used to analyze the qualitative data and were then presented through narrations. The study discovered that the application of school regulations had a favorable and considerable impact on students' academic performance in Mogadishu. The results of this study may help stakeholders and those in charge of policy at the education ministry understand how head teachers might improve students' academic performance by implementing school rules. In conclusion, the head teachers’ school rules implementation had a reasonable affirmative relationship and account for variance in academic performance in secondary schools. It showed that academic performance increases among students with an increase in the level of school rules implementation by the head teacher. For Private Organizations managers, to function most effectively, the study recommends that leaders need to avail themselves for training on how best to manage student discipline in schools in the course of school rules implementation.